Joint Group for Swedish Computer Terminology, questions and answers - Swedish Language Council, Swedish Institute for Language and Folklore (Institute for Language and Folklore, 2026)
Questions and answers from the Joint Group for Swedish Computer Terminology. The dataset contains two files: an Excel file and an XML file. The XML file contains the complete dataset, while the Excel file contains a subset of the dataset. Both files contain a total of 180 questions and answers.

Frågor och svar från Svenska datatermgruppen. Innehåller två filer: en Excel-fil och en XML-fil. XML-filen innehåller den fullständiga datan medan Excel-filen innehåller ett urval av information. Båda filerna omfattar totalt 180 frågor och svar.
Svenska datatermgruppen, frågor och svar
Keywords: language planning; språkvård; loan translations; översättningslån; terminology work; terminologiarbete; terminology; terminologi; translation strategies; översättningsstrategier; Languages and Literature; Språk och litteratur